2021
DOI: 10.1039/d1tb01403j
|View full text |Cite
|
Sign up to set email alerts
|

Review on recent progress in metal–organic framework-based materials for fabricating electrochemical glucose sensors

Abstract: Diabetes is a type of disease that threatens human health, which can be diagnosed based on the level of glucose in the blood. Recently, various MOF-based materials have been developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 160 publications
0
37
0
Order By: Relevance
“…19 Recently, our group has reviewed MOF based materials as efficient sensors for enzymatic and nonenzymatic glucose sensors. 20 Additionally, various MOF-derived material substances like cobalt-MOF, 21 zirconium-MOF, 22 copper-MOF, 23 and the rest of the modified carbon-derived materials are exhibited to have a synergistically improved impact on multiple molecule oxidation and sensing. Lately, Wu et al suggested copper BTC/GS by combining Cu-based metal–organic frameworks (Cu-BTC, BTC = 1,3,5-benzene tricarboxylic acid) and highly conductive ball-mill-exfoliated graphene (Cu-BTC@GS).…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, our group has reviewed MOF based materials as efficient sensors for enzymatic and nonenzymatic glucose sensors. 20 Additionally, various MOF-derived material substances like cobalt-MOF, 21 zirconium-MOF, 22 copper-MOF, 23 and the rest of the modified carbon-derived materials are exhibited to have a synergistically improved impact on multiple molecule oxidation and sensing. Lately, Wu et al suggested copper BTC/GS by combining Cu-based metal–organic frameworks (Cu-BTC, BTC = 1,3,5-benzene tricarboxylic acid) and highly conductive ball-mill-exfoliated graphene (Cu-BTC@GS).…”
Section: Introductionmentioning
confidence: 99%
“…During diabetes, the level of the inflammatory factor TNF-α is also elevated [ 60 ]. In recent years, MOF nanoparticles have been used to enhance the catalytic activity of immunosensors by virtue of their open metal sites and tunable microporous structures [ 65 , 66 ]. Therefore, many MOF-based electrochemiluminescence (ECL) biosensors have been developed for the detection of diabetes, including blood glucose sensors [ 67 , 68 , 69 ], acetone and isopropanol sensors [ 70 , 71 , 72 ], and other sensors [ 57 , 58 , 59 , 60 ].…”
Section: Application Of Mofs In Diabetes Diagnosismentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), a class of porous crystalline materials composed of metal nodes and organic linkers, are of distinct attention as catalysts for glucose detection, owing to their numerous active sites, tunable morphologies and various composition [80][81][82]. Precise detection of glucose is vital for the identification of diabetes, where efficient and sensitive biosensors for glucose detection are highly desired.…”
Section: Metal-organic-framework Derived Bimetallic Nanomaterials Based Glucose Detectionmentioning
confidence: 99%